Out-of-Partnership Births in East and West Germany - Uwe Jirjahn; Cornelia Struewing (Global Labor Organization (GLO), 2019)
Using data from the German Socio-Economic Panel (SOEP), we show that single women in East Germany are significantly more likely to give birth to a child than single women in West Germany. This applies to both planned and unplanned births. Our analysis provides no evidence that the difference between East and West Germany can be explained by economic factors or the higher availability of child care in East Germany. This suggests that the difference in out-of-partnership births is rather driven by behavioral and cultural differences. However, these behavioral and cultural differences do not only reflect different gender role models that evolved under the former communist regime in East Germany and the democratic one in West Germany. Partly, they also reflect a long historical divide that predates the 1945 separation of Germany.
Keywords: J12; J13; P20; 330; Unpartnered birth; gender role models; culture; East Germany; West Germany; politico-economic systems